Pseudecheneis maurus, a new species of glyptosternine catfish (Teleostei: Sisoridae) from Central Vietnam - Ng, Heok Hee; Tan, Heok Hui (Zootaxa, 2007)
A new species of sisorid catfish, Pseudecheneis maurus, is described from the Song Thuy Loan drainage in Central Vietnam. Pseudecheneis maurus can be distinguished from congeners in having a combination of a very short adipose-fin base (1.2 times length of anal-fin base vs. 1.5–2.0 times; 15.7% SL vs. 17.6–30.6), thoracic adhesive apparatus with sulcae not meeting at midline and the absence of distinct pale spots on the body.